How to make sure the permanent decorative tattoo. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2015)
Epidemiological data on the tattoo say that in Italy in the population over the age of 12 years about 13% of the subjects had one or more tattoos. This incidence is similar in other European countries, while in the US the percentage of tattooed among subjects aged 18-50 years is nearly 25%. 3.3% of tattooed subjects have side effects, mainly related to the red color. However, tattoos are often used by doctors with considerable advantages for both patients and healthcare systems; tattoos with medical purposes, which in some regions are included in the basic levels of care, can play a key role in the drafting of legislation on the tattoo, still absent in Italy and in Europe, able to increase the safety of tattoo with benefits of the tattoo artist and the tattooed subject.